(untitled) (Journal of Technology and Operations Management, 2022)
Gamelan Wirun Palu Gongso Industry is one of the businesses in the informal sector that produces several gamelan instruments such as gong, bonang, and kempul that has not paid attention to occupational safety and health (OSH). Based on observations, there are unsafe behaviors and conditions, health problems, and accidents experienced by workers. This study aims to identify hazards in the workplace, determine the highest priority of hazards to be solved, and then provide recommendations for improvement based on the priority. A participatory ergonomic approach is used to solve the problems in this study. ILO-PATRIS Check Sheet is used to identify hazards in the workplace. The Delphi method determines the hazards with the highest priority for improvement. The Delphi method is a group of interaction processes between researchers and a group of experts identified on a particular topic, usually asking a question that allows a communication process to discuss complex problems but does not allow attending in one meeting. The result of the ILO-PATRIS Check Sheet shows 19 sub-aspects in the workplace that need improvements.